2016
DOI: 10.1523/jneurosci.2234-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Functional Connectivity in the Adult Brain and Success in Second-Language Learning

Abstract: There is considerable variability in an individual's ability to acquire a second language (L2) during adulthood. Using resting-state fMRI data acquired before training in English speakers who underwent a 12 week intensive French immersion training course, we investigated whether individual differences in intrinsic resting-state functional connectivity relate to a person's ability to acquire an L2. We focused on two key aspects of language processing-lexical retrieval in spontaneous speech and reading speed-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 63 publications
(11 reference statements)
3
58
1
Order By: Relevance
“…Several studies have proposed statistical approaches to test for the presence of non-stationarity, including the assessment of the variance of the FC time series (Sakoğlu et al, 2010), test statistics based on the FC time series’ Fourier-transform (Handwerker et al, 2012), linear (e.g., variance of correlation series (Hindriks et al, 2016)) and nonlinear test statistics (Zalesky et al, 2014), among others (Chang and Glover, 2010; Keilholz et al, 2013; Laumann et al, 2016). The bulk of the evidence points to the non-stationary nature of BOLD FC, a conclusion that is consistent with recent work suggesting that non-stationarity in BOLD functional connectivity reflects changes in ongoing cognitive processes supporting learning, working memory function, linguistic processing, and executive function (Bassett et al, 2011; Braun et al, 2015; Chai et al, 2016, 2017; Hutchison et al, 2013a). Nonetheless, some of these reports are inconclusive, mainly because test statistics are commonly compared against that of null (stationary) time series and creating such time series with matching covariance structure, spectral properties, and stationary FC to this day remains a challenge (Hindriks et al, 2016).…”
Section: Resultssupporting
confidence: 84%
“…Several studies have proposed statistical approaches to test for the presence of non-stationarity, including the assessment of the variance of the FC time series (Sakoğlu et al, 2010), test statistics based on the FC time series’ Fourier-transform (Handwerker et al, 2012), linear (e.g., variance of correlation series (Hindriks et al, 2016)) and nonlinear test statistics (Zalesky et al, 2014), among others (Chang and Glover, 2010; Keilholz et al, 2013; Laumann et al, 2016). The bulk of the evidence points to the non-stationary nature of BOLD FC, a conclusion that is consistent with recent work suggesting that non-stationarity in BOLD functional connectivity reflects changes in ongoing cognitive processes supporting learning, working memory function, linguistic processing, and executive function (Bassett et al, 2011; Braun et al, 2015; Chai et al, 2016, 2017; Hutchison et al, 2013a). Nonetheless, some of these reports are inconclusive, mainly because test statistics are commonly compared against that of null (stationary) time series and creating such time series with matching covariance structure, spectral properties, and stationary FC to this day remains a challenge (Hindriks et al, 2016).…”
Section: Resultssupporting
confidence: 84%
“…Similar positive correlations between frontal beta power at rest and learning rate were found in both of our previous rsEEG investigations of natural language learning in adulthood 20,25 . These findings add to the increasing body of literature suggesting that characterizations of resting-state brain networks can be used to understand individual differences in executive functioning 26 and complex skill learning more broadly [19][20][21] .…”
Section: Discussionmentioning
confidence: 76%
“…To understand the relative predictive utility of such measures, we included factors known to relate to complex skill learning more generally (e.g., fluid reasoning ability, working memory, inhibitory control), and numeracy, the mathematical equivalence of literacy, as predictors. In addition, the current research adopted a neuropsychometric approach, leveraging information about the intrinsic, network-level characteristics of individual brain functioning which have proven to provide unique predictive utility in natural language learning [19][20][21] . Such an approach allows us to leverage the field of cognitive neuroscience to understand, in a paradigm-free manner, the cognitive bases of learning to program.…”
mentioning
confidence: 99%
“…In a recent review article, Zatorre (2013) discusses findings showing how structural and functional neural connectivity patterns predict individual differences in musical training and speech learning. Other studies have shown similar predictability for a wide array of cognitive abilities including executive function (Barnes et al 2014;Reineberg et al 2015), reading (Koyama et al 2011;Wang et al 2013), second language acquisition (Chai et al 2016), visual perceptual discrimination (Baldassarre et al 2012), and memory recall (King et al 2015). In the motor domain, Tomassini et al (2011) demonstrated that individual differences in both functional and structural magnetic resonance imaging (MRI) measures correlate with the acquisition of a novel visuomotor tracking skill through active movement training.…”
mentioning
confidence: 88%